The Technology of Robusta Coffee Decaffeination for Small and Medium Scale of Industries - Suharman, Suharman; Gafar, Patoni A (Jurnal Dinamika Penelitian Industri, 2017)
The research on the Technology of Robusta Coffee (Coffea canephora L.) Decafeinationfor Small and Medium Scale of Industries had been carried out. The purpose of the research was to get the technology of decaffeination on robusta coffee. The research was conducted by using Completely Randomized Design (RAL) with raw material samples taken from specified area (purposive sampling), there wereMuara Enim, Pagar Alam and Lubuk Linggau Districts and then combined by composites. The main apparatus were 10 liter silindric container and 10 liter steamer with simple condenser. The treatments include boiling and steaming coffee beans at 100Â°C for 30, 60 and 90 minutes. The results show that the process of decreasing caffeine (decaffeination) by boiling 30, 60 and 90 minutes resulted caffeine content of 0.66%, 0.45% and 0,40% each; whereas by steaming resulted 1.65%, 0.42% dan 0.45% each. The results of this research can be applied by small and medium industres (SMIs) because simple and low cost.